Agreement Test of Documentation of Visual Inspection with Acetic Acid â€œDoVIAâ€ and Colposcopy findings as a Screening Tool for Cervical Cancer: Kesesuaian Hasil Tes Dokumentasi Inspeksi Visual dengan Asam Asetat (DoVIA) dan Kolposkopi sebagai Alat Skrining untuk Kanker Servik - Laila Nuranna; Renny Surya Wardany; Gatot Purwoto; Tofan W. Utami; Lex Peters (Indonesian Journal of Obstetrics and Gynecology, 2020)
Abstract Objective: To find out the suitability of Documentation of Visual Inspection with Acetic Acid (DoVIA) result compare to colposcopy result as a method of cervical cancer screening. Method: This is a descriptive study using cross sectional design that took place from April 2017 until March 2019. One hundred eighty two sampels of documentation photographs taken by the researcher were included. The photographs were reviewed by the 3 selected reviewers: oncology and gynecology consultant, obstetry and gynecology resident, and general practitioner that were trained about DoVIA and colposcopy. The review was based on kappa test which assessed the sharpness, squamo-columnar junction and white epitel visualization on the cervix. Results: Kappa score on DoVIA versus colposcopy was 0,717 (good). Inter-rater test was performed to assess consistency and the result was 0,764 (good) between consultant and resident, 0,703 (good) between consultant and general practitioner. Conclusion: Kappa test of IVA documentation â€DoVIAâ€ gives a good kappa value, so that it is expected to be an alternative screening for precancerous lesions. Keyword: cervical cancer screening, VIA, DoVIA, colposcopy, mini colposcopy Abstrak Tujuan: Untuk menemukan kesesuaian antara dokumentasi hasil inspeksi visual dengan asam asetat (DoVIA) dibanding dengan hasil kolposkopi sebagai metode skrining kanker serviks. Metode Penelitian deskripsi ini menggunakan desain cross sectional yang telah dilakukan sejak April 2017 hingga Maret 2019. Seratus delapan puluh dua sampel dokumentasi telah diambil oleh peneliti telah dimasukkan menjadi sampel. Hasil dokumentasi telah dinilai oleh 3 penilai yang terdiri dari konsultan onkologi dan ginekologi, residen obstetri dan ginekologi, dan dokter umum yang telah dilatih untuk DoVIA dan kolposkopi. Hasil penilaian dilakukan berdasarkan kappa untuk menilai ketajaman, sambungan skuamos kolumner dan visualisasi lesi putih di serviks Hasil Skor kappa pada DoVIA dibanding kolposkopi adalah 0,717 (baik). Hasil prbandingan penilaian antar penilai yang ditunjukkan untuk menilai konsistensi dan hasil adalah 0,764 (baik) antara konsultan dan residen, 0,703 (baik) antara konsultan dan dokter umum. Kesimpulan Tes kappa pada dokumentasi IVA (DoVIA) memberikan hasil kappa baik, sehingga DoVIA diharapkan dapat menjadi alternatif skrining untuk lesi prakanker. Kata kunci : skrining kanker serviks, IVA, DoVIA, kolposkopi, minikolposkopi